9 - International Student Recruitment: South African Rationales - Bolsmann, Chris; Miller, Henry (Journal of Higher Education in Africa, 2008)
In this paper, we focus on the rationales for the recruitment of international stu- dents to universities in South Africa. Through the use of in-depth interviews with international officers at a cross-section of South African universities, we argue that there are competing and complementary rationales for the recruitment of international students. Some South African universities follow international trends in terms of international student recruitment while others adopt a different ap- proach. The analysis locates the rationales of international student recruitment as part of an internationalisation process within the context of globalisation.